THE ROLE OF PERSONALIZED EDUCATION TOOLS IN COMPUTER PROGRAMMING LEARNING - Junus, Fadhla Binti (Proceedings of the International Conference on Education, 2017)
The proliferation of information and communication technology (ICT) which is followed by the high demand of ICT tools, especially smartphones, has transformed the face of global learning, as everybody would be able to educate themselves without having to commute from home to school. This phenomenon has emerged a tutorial generation who has been educated by personalized education tools in the form of mobile-based and/or web-based applications that support any kind of knowledge they are interested in. This paper depicted a conducted research question whether those applications will vanish the traditional teaching model which was believed as high consuming in cost, time, and effort. The respondents were the students and lecturers of the vocational information technology program at UIN Ar-Raniry. During the research, they were given the top five independent learning applications related to programming courses, then they were requested to review at the same courses that was served by the most highly impact of MOOC services such as Coursera, Edx, and Udacity. The experiences of the participants were recorded and noted, then analyzed by QDA Miner software which summarized that ICT education tools assisted them to sharpen their understanding of the course content because they could learn at their own pace. Such education model is expected to empower a community within university preparing the formal institutions to adopt the new form of education. In the future, a further research will be needed on discussing a basic standard in the development of educational applications that is relevance to the curriculum.